2015
DOI: 10.1088/0963-0252/24/3/034003
|View full text |Cite
|
Sign up to set email alerts
|

Continuum emission-based electron diagnostics for atmospheric pressure plasmas and characteristics of nanosecond-pulsed argon plasma jets

Abstract: Electron diagnostics based on electron-neutral atom (e-a) bremsstrahlung in the UV and visible range emitted from atmospheric pressure plasmas is presented. Since the spectral emissivity of the e-a bremsstrahlung is determined by electron density (n e) and mean electron temperature (T e) representing the Maxwellian electron energy distribution, their diagnostics is possible. As an example, emission spectra measured from capacitive discharges are presented, which show good agreement with the theoretically calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 34 publications
1
48
0
Order By: Relevance
“…A strong initial n e overshoot with a maximum of 7 × 10-13 cm −3 and a mean electron energy of 0.1-3.0 eV were observed in an argon plasma jet driven by a 3.5 kV positive dc pulse with a pulse width of 500 ns and a repetition frequency of 5 kHz [78]. Using a similar setup, Park et al [84] reported that the time-averaged n e was 1 × 10 9 cm −3 and T e was (1.0-2.5) eV via a comparison of the absolute intensity of continuum emission spectrum with the theoretically calculated neutral bremsstrahlung emissivity.…”
Section: Plasma Jetmentioning
confidence: 89%
See 4 more Smart Citations
“…A strong initial n e overshoot with a maximum of 7 × 10-13 cm −3 and a mean electron energy of 0.1-3.0 eV were observed in an argon plasma jet driven by a 3.5 kV positive dc pulse with a pulse width of 500 ns and a repetition frequency of 5 kHz [78]. Using a similar setup, Park et al [84] reported that the time-averaged n e was 1 × 10 9 cm −3 and T e was (1.0-2.5) eV via a comparison of the absolute intensity of continuum emission spectrum with the theoretically calculated neutral bremsstrahlung emissivity.…”
Section: Plasma Jetmentioning
confidence: 89%
“…For further insights, the electrons in plasma jets has also been characterized using various electron diagnostic techniques, such as laser Thomson scattering [76][77][78], laser interferometry [79], Stark broadening of hydrogen atomic lines [80][81][82], and continuum radiation [84]. The line broadening method has been widely used for most electron studies in atmospheric-pressure plasmas, particularly in microwave-and radio-frequency-excited plasmas because of their high n e .…”
Section: Plasma Jetmentioning
confidence: 99%
See 3 more Smart Citations